Los riesgos laborales en la empresa minera y las competencias del trabajador social en su accionar profesional - Peña Farfán, Marco Vinicio (My University, 2019)
The objective of this work is "To analyze the occupational risks in the mining company, through the review of scientific articles in indexed journals, for the identification of the competences of the Social Worker". In the first place, a bibliographic review was carried out in correspondence to the labor risks in the mining company based on the following authors Gómez, Hernández, and Méndez (2014), Camacho and Mayorga (2017), Neffa (2015), Nieto (2014), Patlán (2016), Ramírez (2016), Viloria, Pertúz, Daza, and Pedraza (2016), Velasco (2017), Pérez, Espinoza and peralta (2016), Céspedes and Martínez (2016), Vega, Moreno, Márquez, Gonzáles and Pérez (2017). Preventing accidents at work is important for the company, beyond compliance with a standard, helps improve the working conditions of workers in order to achieve better labor productivity by ensuring the rights of the worker. It has been shown that training in emergencies, self-care, postural hygiene; the risk assessment of workplaces, equipment, physical, chemical and biological agents, psychosocial factors, etc., reduce labor risks and conflicts, which results in productive time for work organizations. For the development of research, the methodology of documentary bibliographic research is applied as the main tool for the description of the problem, the results of the research that is evidenced through the prevention plan framed in the proposal with the objective of being able to intervene in professional way in the prevention of occupational risks that occur in the mining company.
El presente trabajo tiene como objetivo “Analizar los riesgos laborales en la empresa minera, mediante la revisión de artículos científicos en revistas indexadas, para la identificación de las competencias del Trabajador Social”. En primer lugar, se realizó una revisión bibliográfica en correspondencia a la problemática de riesgos laborales en la empresa minera en base a los siguientes autores Gómez, Hernández, y Méndez (2014), Camacho y Mayorga (2017), Neffa (2015), Nieto (2014), Patlán (2016), Ramírez (2016), Viloria, Pertúz, Daza, y Pedraza (2016), Velasco (2017), Pérez, Espinoza y peralta (2016), Céspedes y Martínez (2016), Vega, Moreno, Márquez, Gonzáles y Pérez (2017). Prevenir los accidentes de trabajo es importante para la empresa, más allá del cumplimiento de una norma, ayuda a mejorar las condiciones laborales de los trabajadores con la finalidad de lograr una mejor productividad laboral asegurando los derechos del trabajador. Se ha evidenciado que realizar capacitaciones en emergencias, autocuidado, higiene postural; la evaluación de riesgos de los lugares de trabajo, equipos, agentes físicos, químicos y biológicos, factores psicosociales, etc., disminuyen los riesgos y conflictos laborales lo cual redunda en tiempo productivo para las organizaciones de trabajo. Para el desarrollo de la investigación se aplica como metodología la técnica de investigación bibliográfica documental como herramienta principal para la descripción del problema, los resultados de la investigación que se evidencia a través del plan de prevención enmarcado en la propuesta con el objetivo de poder intervenir de manera profesional en la prevención de los riesgos laborales que se producen en la empresa minera.
Keywords: RIESGO LABORAL; TRABAJADOR; PREVENCION; ORGANIZACION